2002
DOI: 10.1161/01.res.0000030861.13850.f1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Mediates Enhanced Spontaneous and Agonist-Induced Contraction in Aorta of Deoxycorticosterone Acetate-Salt Hypertensive Rats

Abstract: Abstract-Arteries from deoxycorticosterone acetate (DOCA)-salt and N -nitro-L-arginine (L-NNA) hypertensive but not normotensive rats develop spontaneous tone. LY294002 and wortmannin, phosphoinositide 3-kinase (PI3-kinase) inhibitors, eliminate spontaneous tone. We hypothesized that PI3-kinase protein and/or activity was increased in hypertension and contributed to the observed enhanced contractility. PI3-kinase activity assays revealed 2-fold higher activity in thoracic aorta from DOCA-salt [systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
104
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 44 publications
(46 reference statements)
13
104
2
Order By: Relevance
“…PI3-K reduces force in vascular smooth muscle in response to either membrane depolarization or receptor activation (Komalavilas et al, 2001;Northcott et al, 2002;Su et al, 2004). Indeed, Su and colleagues suggested that PI3-K performs at least two distinct roles in the regulation and/or modulation of force (Su et al, 2004).…”
Section: Concerning Contractile Responses Several Studies Have Demonmentioning
confidence: 99%
See 3 more Smart Citations
“…PI3-K reduces force in vascular smooth muscle in response to either membrane depolarization or receptor activation (Komalavilas et al, 2001;Northcott et al, 2002;Su et al, 2004). Indeed, Su and colleagues suggested that PI3-K performs at least two distinct roles in the regulation and/or modulation of force (Su et al, 2004).…”
Section: Concerning Contractile Responses Several Studies Have Demonmentioning
confidence: 99%
“…The second major pathway is potentially protein kinase Cdependent, and enhances force independently of changes in either Ca 2+ or myosin light chain (MLC) phosphorylation levels. PI3-K has also been implicated in the pathology of hypertensioninduced vascular hypersensitivity and ethanol-induced cerebral contractions (Yang et al, 2001;Northcott et al, 2002). Watts and coworkers reported that an enhancement of PI3-K activation seems to underlie the increase in spontaneous vascular tone observed in both deoxycorticosterone acetate (DOCA)-salt and N-nitro-L-Arg hypertensive rats (Northcott et al, 2002.…”
Section: Concerning Contractile Responses Several Studies Have Demonmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Moreover, Class IA regulatory p85␣ subunit-associated PI3-kinase activity and PI3-kinase protein expression, specifically the p110␦ subunit, was upregulated in aorta from DOCA-salt hypertensive rats compared with normotensive sham animals. 7 It is not apparent how different p110 isoforms play specific functional roles in cells. Moreover, the aorta, a conduit artery, is the tissue in which most of the characterization of PI3-kinase and hypertension has been studied and only has a relatively small influence on blood pressure.…”
mentioning
confidence: 99%